Stimulus control depends on the subjective value of the outcome. Issue 2 (20th August 2020) - Cowie, Sarah; Gomes‐Ng, Stephanie; Hopkinson, Brooke; Bai, John Y.H.; Landon, Jason
Abstract : Stimuli that provide information about likely future reinforcers tend to shift behavior, provided a reliable relation between the stimulus and the reinforcer can be discriminated. Stimuli that are apparently more reliable exert greater control over behavior. We asked how the subjective value (measured in terms of preference) of reinforcers associated with stimuli influences stimulus control. Five pigeons worked on a concurrent chains procedure in which half of all trials ended in a smaller reinforcer sooner, and the other half in a larger reinforcer later. In Signaled trials, the color and flash duration on the keys in the initial link signaled the outcome of the trial. In Conflicting probe trials, the color and the flash duration signaled conflicting information about the outcome of the trial. Choice in Signaled trials shifted toward the signaled outcome, but was never exclusive. In Conflicting probe trials, control was divided idiosyncratically between the 2 stimulus dimensions, but still favored the outcome with the higher subjective value. Thus, stimulus control depends not only on the perceived reliability of stimuli, but also on the subjective value of the outcome.